2016
DOI: 10.3389/fevo.2016.00032
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Various Land Reclamation Scenarios on the Succession of Soil Bacteria, Archaea, and Fungi Over the Short and Long Term

Abstract: Ecological restoration of mining areas has mainly focused on the succession dynamics of vegetation and the fate of microbial communities remains poorly understood. We examined changes in soil characteristics and plant and microbial communities with increasing reclamation period in an open coal mine. Bacterial, archaeal and fungal communities were assessed by tag-encoded 454 pyrosequencing. At the phylum level, Proteobacteria, Crenarchaeota, and Ascomycota had the highest detected relative abundance within bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 45 publications
3
14
0
Order By: Relevance
“…Further, stochastic (e.g., dispersal by wind, ecological drift) and deterministic processes can interact to influence microbial community composition in soil (Caruso et al, 2011;Cline and Zak, 2014;Ferrenberg et al, 2013;. While soil microbial community assembly in anthropogenically disturbed soils is not widely studied, deterministic factors such as bulk density, pH, and plant species can be influential in shaping communities following physical disturbance of the soil profile (Calderón et al, 2000;da C Jesus et al, 2009;Li et al, 2016).…”
Section: Ecological Successionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, stochastic (e.g., dispersal by wind, ecological drift) and deterministic processes can interact to influence microbial community composition in soil (Caruso et al, 2011;Cline and Zak, 2014;Ferrenberg et al, 2013;. While soil microbial community assembly in anthropogenically disturbed soils is not widely studied, deterministic factors such as bulk density, pH, and plant species can be influential in shaping communities following physical disturbance of the soil profile (Calderón et al, 2000;da C Jesus et al, 2009;Li et al, 2016).…”
Section: Ecological Successionmentioning
confidence: 99%
“…To date, there has been some insight into how microbial communities respond to surface mining using chronosequence-based approaches (Banning et al, 2008;Li et al, 2016;Sun et al, 2017). However, the relative influence of stochastic and deterministic factors on microbial communities during succession following surface mining remains unexplored.…”
Section: Surface Mining and Microbial Community Assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…Establishment of a soil microbial community is crucial for newly reclaimed ecosystems to function because soil microbes play a vital role in the acquisition and cycling of nutrients, formation of soil structure, energy flow, plant diversity and productivity in terrestrial ecosystems (Mummey et al, 2002). Soil microbial biomass, diversity, community structure and function have been used to assess the effects of both the vegetation used in reclamation and length of time since reclamation began on the quality of mine soil (Chodak et al, 2009;Li et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that soil microbial community succession of bacterial, archaeal and, fungal communities were assessed by tag encoded 454 pyrosequencing. At the phylum level, Proteobacteria, Crenarchaeota, and Ascomycota had the highest detected relative abundance within bacteria, archaea, and fungi, respectively (Li et al 2016).…”
Section: Introductionmentioning
confidence: 98%